PERAN DINAS LINGKUNGAN HIDUP KABUPATEN KARANGASEM DALAM PENGENDALIAN PENCEMARAN LINGKUNGAN SEBAGAI AKIBAT KEGIATAN PETERNAKAN AYAM DI DESA PESEDAHAN, KECAMATAN MANGGIS, KABUPATEN KARANGASEM, BALI - Suryaningsih, Sayu Putri; Apriliani, Kadek (Jurnal Hukum Mahasiswa, 2024)
This research uses a type of empirical legal research, with a factual and sociological legal approach. Data was collected using interview and observation techniques. The results of the research can be stated that: 1) the role of the Karangasem Regency Environmental Service includes prevention through guidance, supervision, providing education and training to the community, as well as mitigation and recovery actions in collaboration with all levels of society. 2) Supporting factors for the role of the Environmental Service from the external side, namely increasing public demands and awareness regarding environmental health, internal factors, namely support from regional and central governments in improving environmental health. While the inhibiting factor from the external side is the lack of awareness of livestock owners and the public regarding environmental health, from the internal side is the lack of Environmental Service employees to go to the field to take action and monitor environmental pollution that occurs.